2016
DOI: 10.4049/jimmunol.1501593
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell–Specific Gata3 Ablation Identifies the Maturation Program Required for Bone Marrow Exit and Control of Proliferation

Abstract: NK cells are innate lymphocytes capable of eliciting an innate immune response to pathogens. NK cells develop and become mature in the bone marrow (BM) before they migrate out to peripheral organs. Although the developmental program leading to mature NK cells has been studied in the context of several transcription factors, the stage-specific role of GATA3 in NK cell development has been incompletely understood. Using NKp46-Cre-Gata3fl/fl mice in which Gata3 deficiency was induced as early as the immature stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 71 publications
1
44
0
1
Order By: Relevance
“…The TF GATA binding protein 3 (Gata3) is essential for the generation of thymic NK (tNK) cells, which are distinct from classical NK cells in their reliance on IL‐7 signaling, but not T‐bet or ID2, for development . Compared with tNK cells, the role of Gata3 in ‘classical’ NK cell development is more nuanced.…”
Section: Transcription Factors That Regulate Nk Cell Development and mentioning
confidence: 99%
See 2 more Smart Citations
“…The TF GATA binding protein 3 (Gata3) is essential for the generation of thymic NK (tNK) cells, which are distinct from classical NK cells in their reliance on IL‐7 signaling, but not T‐bet or ID2, for development . Compared with tNK cells, the role of Gata3 in ‘classical’ NK cell development is more nuanced.…”
Section: Transcription Factors That Regulate Nk Cell Development and mentioning
confidence: 99%
“…Compared with tNK cells, the role of Gata3 in ‘classical’ NK cell development is more nuanced. Although early studies reported normal numbers of Gata3‐deficient NK cells in fetal liver chimeric mice, later work showed that genetic deletion of Gata3 at the iNK stage led to reduced numbers of NK cells in the BM and spleen . Furthermore, Gata‐3‐deficient NK cells maintain cytotoxicity against tumor target cells, but exhibit an immature phenotype characterized by higher CD27 expression, lower expression of T‐bet, CD11b, CD43, and several Ly49 receptors, as well as diminished IFN‐ γ production in vitro …”
Section: Transcription Factors That Regulate Nk Cell Development and mentioning
confidence: 99%
See 1 more Smart Citation
“…These cells express the IL‐2Rβ chain (CD122), Sca‐1, IL‐7Rα, and ID2 but lacked markers typically expressed on fully differentiated mature NK cells such as NK1.1, NKp46, and CD49b . In the bone marrow, this progenitor further committed into NK progenitor (NKP) and subsequently into immature and mature NK cells under the influence of a core transcription program including but not restricted to Id2 , Gata3 , Nfil3 , Klf2 , Eomes , Tbx21 , Tcf7 , Tox, and Ets‐1 (Figure ) . Interestingly, NFIL3 expression is essential for the development of all ILC subsets but appears to be only required early and transiently to implement the ILC program as Nfil3 deletion in ID2 + mature NK cells does not affect NK cell survival or function …”
Section: Innate Lymphoid Cell Subsetsmentioning
confidence: 99%
“…Critical extracellular signals influencing ILC functions and mediating ILC plasticity are depicted. Networks were designed based on Ch IP data or reporter assays (thick lines) together with gene deletion or overexpression systems (regular lines) . Nonexpressed genes are depicted in gray.…”
Section: Innate Lymphoid Cell Subsetsmentioning
confidence: 99%